Selective disruption of dopamine D2 receptors in pituitary lactotropes increases body weight and adiposity in female mice - Pérez Millán, María Inés (2014)
Prolactin, a pleiotropic hormone secreted by lactotropes, has reproductive and metabolic functions. Chronically elevated prolactin levels increase food intake, but in some hyperprolactinemic states such as in the global dopamine D2 receptor (D2R) knockout mouse, food intake is not increased. Here, we conduct a cell-specific genetic dissection study using conditional mutant mice that selectively lack D2Rs from pituitary lactotropes (lacDrd2KO) to evaluate the role of elevated prolactin levels without any confounding effect of central D2Rs on motor and reward mechanisms related to food intake. LacDrd2KO female mice exhibited chronic hyperprolactinemia, pituitary hyperplasia, and a preserved GH axis. In addition, lacDrd2KO female but not male mice evidenced increased food intake by three months of age and, from five months onwards their body weights were heavier. A marked increment in fat depots, adipocyte size, serum triglyceride and non-esterified fatty acid levels, and a decrease in lipolytic enzymes in adipose tissue were evidenced. Furthermore, lacDrd2KO female mice had glucose intolerance but a preserved response to insulin. In the hypothalamus Npy mRNA expression was increased, and Pomc and Ppo mRNA levels were unaltered (in contrast to results in global D2R knockout mouse). Thus, the orexigenic effect of prolactin, and its action on hypothalamic Npy expression were fully evidenced, leading to increased food intake and adiposity. Our results highlight the metabolic role of prolactin and illustrate the value of studying cell-specific mutant mice to disentangle patho-physiological mechanisms otherwise masked in null allele mutants or in animals treated with pervasive pharmacological agents.